"So Much Potential:" Latino/a Immigrant Emerging Adults, Legal Status, and Educational Participation - Laura M. Gonzalez; Isabelle Ong Gaffney; Yesenia Mejia (Journal of Community Engagement and Scholarship)
Immigrant young adults without permanent legal status face a complicated set of issues as they try to integrate into adult society in the U.S. In this participatory research study, Latino/a emerging adult participants (n = 7) shared their perspectives about what it was like to live with Deferred Action for Childhood Arrivals (DACA), with temporary or unauthorized legal status, or in a mixed immigrant-status family within communities in central North Carolina. Specifically, participants were asked how those experiences impacted their educational pathways as a key marker of the ease or difficulty of community integration and adult role taking. The study was a qualitative participatory action research study, and the interview data were analyzed using interpretive phenomenological analysis (IPA). Relational cultural theory (RCT) was utilized to illuminate participants’ contexts and experiences, and how they encountered connection/warm welcome or disconnection/chilly welcome. Three key themes emerged from participants’ narratives: The first, self/identity, encompasses both experiences of belonging and backlash from the local community. The second, descriptions of context, details the supports and barriers to integration that were present. The third theme, responses to context, highlights how the participants engaged in self-advocacy at times, but also noted how the lack of basic rights was an obstacle for themselves and their peers. Together, these insights present critical considerations for understanding and supporting young adult immigrants and their integration/participation in U.S. communities.